Determinants of Academic Performance of the Students of Public Universities in Bangladesh - Rashed Alam; Rafiqul Islam (Athens Institute for Education and Research, 2022)
Education is one of the most important factors in producing human resources. University education can be influenced by many factors that affect students' quality of academic performance. The main focus of this study is identifying the influencing factors that are significantly associated with the academic performance of universities students. Data were extracted from the various departments of two public universities. Data analysis by Contingency and logistic regression were used to identify the determinants of academic performance of the students. Among the students, 56.8% were male and 43.2% were female most of them are Muslims and unmarried. 75.1% of students came from rural areas, only 15% of students' mothers were higher educated and 65% of student's family status was middle class. Higher educated mother, HSC and SSC results, admitted to an expected university, admitted present department by their own choice, study environment in the department and use of the internet had significant effects on the results of 1st year of the students. The findings concluded that increase and improve students' academic performance are some crucial steps regarding securing admission first choice of the department and advising about peer influence should be taken into consideration.